2021
DOI: 10.3389/fimmu.2021.644725
|View full text |Cite
|
Sign up to set email alerts
|

From ELISA to Immunosorbent Tandem Mass Spectrometry Proteoform Analysis: The Example of CXCL8/Interleukin-8

Abstract: With ELISAs one detects the ensemble of immunoreactive molecules in biological samples. For biomolecules undergoing proteolysis for activation, potentiation or inhibition, other techniques are necessary to study biology. Here we develop methodology that combines immunosorbent sample preparation and nano-scale liquid chromatography—tandem mass spectrometry (nano-LC-MS/MS) for proteoform analysis (ISTAMPA) and apply this to the aglycosyl chemokine CXCL8. CXCL8, the most powerful human chemokine with neutrophil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Such a method is essential, as the proteoforms cannot be distinguished by standard immunoassays like ELISAs or western blot since (a) available antibodies fail to discriminate between the proteoforms and (b) western blot cannot detect minor differences in molecular mass due to the subtle proteolysis. With this technique, all the natural CXCL8 proteoforms were found in the synovial fluids of arthritic patients [ 98 ]. Since proteases truncating CXCL8 are usually upregulated in inflammatory conditions, detecting different CXCL8 proteoforms with highly differential activity in samples from patients with inflammatory diseases will be relevant.…”
Section: The Inflammatory Chemokine Cxcl8mentioning
confidence: 99%
“…Such a method is essential, as the proteoforms cannot be distinguished by standard immunoassays like ELISAs or western blot since (a) available antibodies fail to discriminate between the proteoforms and (b) western blot cannot detect minor differences in molecular mass due to the subtle proteolysis. With this technique, all the natural CXCL8 proteoforms were found in the synovial fluids of arthritic patients [ 98 ]. Since proteases truncating CXCL8 are usually upregulated in inflammatory conditions, detecting different CXCL8 proteoforms with highly differential activity in samples from patients with inflammatory diseases will be relevant.…”
Section: The Inflammatory Chemokine Cxcl8mentioning
confidence: 99%
“…The 69 aa form is most active in in vitro chemotactic assays. 28) There are four cysteine residues forming two disulfide linkage (cysteine 7-cysteine 34 and cysteine 9-cysteine 50) and 14 basic aa residues (lysine and arginine), which confer the basicity required for the binding of IL-8 to heparan sulfateproteoglycan without N-glycosylation sites. 29) G.M.…”
Section: Odyssey To the Discovery Of Il-8mentioning
confidence: 99%
“…However, this is currently impractical given the batch testing requirement of commercial kits, which have been designed for research purposes only rather than clinical practise. More recent studies have shown the quantification of cytokines and chemokines is moving towards proteomic analysis using tandem mass spectrometry, 63 , 64 , 65 , 66 which provides a promising future opportunity.…”
Section: Discussionmentioning
confidence: 99%